Two Cheers and a Pint of Worry: An On-Line Course in Political and Social Philosophy - Heath, Eugene F. (Online Learning, 1998)
During the past decade there have been numerous efforts to reinvigorate distance education; some of these have involved video technology, but others have made use of computers and advances in the design of computer software. In 1995, the State University of New York, funded by a major grant from the Sloan Foundation, embarked upon the creation of an "on-line" learning program--a set of asynchronous and distance learning courses delivered solely via computer. In what follows, I detail the genesis and structure of a course in political and social philosophy that I designed (and taught) for this project. After some preliminary comments on the "virtual classroom”. I illustrate the design of the course, and then offer a brief qualitative assessment. I close the essay with some cautionary reflections on computer-mediated education. Athough my initial skepticism about such courses has been modified, I still believe that there is something valuable about the direct, face-to-face, encounter of teacher and student that is not easily compensated for in computer-mediated learning.